The Relationship Between Organizational Social Capital, Organizational Identity and Organizational Trust Levels of Academicians in Sports Education Institutions - Erdal Taşgın; Abdil Arı (Selcuk University, 2023)
This study was conducted to reveal whether there is a relationship between the organizational social capital and organizational identification perceptions of academics in institutions providing sports education and their levels of organizational trust. In the analysis of the data,in order to reveal the relationship between the organizational social capital, organizational identification and organizational trust levels of academicians, the Pearson Moments Product Correlation Coefficient (r) technique was used. As a result of the research, it was found that the highest perceptions of the academicians in institutions providing sports education about social capital are bridging social capital, the lowest organizational social capital is followed by unifying social capital and linking social capital dimensions; In general, it was judged that academicians' perceptions of bridging, unifying and bonding social capital regarding their institutions are at a "moderate" level, that is, they are not satisfied with their communication in these dimensions of organizational social capital (linking, linking, bridging). It was determined that the highest perceptions of the academicians in sports education institutions regarding organizational identification are in the emotional organizational identification dimension, followed by the cognitive organizational identification dimension, in general, the emotional identification of the academicians about their institutions is high, and their cognitive identification is at the "medium" level. It has been determined that the highest perceptions of the academicians in institutions providing sports education about organizational trust are trust in the manager, followed by the trust in the organization dimension, and the dimensions of trust in the administrator and trust in the organization, in general, are at the "medium" level. It has been determined that there are medium and high-level positive relationships between the dimensions of the academicians in institutions providing sports education, organizational social capital, organizational identification and organizational trust in general.